Reprodução induzida de machos de lambari-do-rabo-amarelo (Astyanax lacustris) com hormônio Kisspeptina - Andreia Regina Konzen Freitas (2022)
KONZEN-FREITAS, A.R., Induced reproduction of lambari (Astyanax lacustris) with kisspeptin hormone. 2022. 42p. Dissertation – Faculty of Veterinary Medicine and Animal Science, Federal University of Mato Grosso do Sul, Campo Grande, MS, 2022. Carp pituitary extract is the main reproductive inducer used in fish, but it has been questioned in recent years, mainly considering the lack of hormonal standardization. In this sense, many reproductive inducers have been evaluated in fish. Among these, kisspeptin should be highlighted, which is produced from the hypothalamus and causes a cell-cell communication cascade, leading to the production of luteinizing hormone and follicle-stimulating hormone in the pituitary. The aim of the study was to evaluate the reproductive performance of the yellow-tailed lambari (Astyanax lacustris) induced with the inducer kisspeptin. 49 males of reproductive age were used. Three levels of kisspeptin were evaluated: 0.020, 0.050 and 0.080 mg/kg of body weight in a single dose. Additionally, a group of fish induced with the standard protocol with carp pituitary extract - EHC (2.5 mg/kg in a single dose) and a group in which saline solution was applied were evaluated. 10 replicates per treatment were used. Semen was collected after 270 degree-hours for the group of fish that received kisspeptin and 160 degree-hours for the group induced with EHC and saline. The sperm concentration did not differ between the different treatments (between 0.8 and 1.03 x 109 sperm/mL). The median of total motility values were higher (P<0.05) in fish induced with EHC (28.8%) in relation to fish induced with different levels of kisspeptin (between 13 and 14.7%) and with serum physiological (13.2%). The same behavior was observed for the variables curvilinear velocity, average velocity of trajectory, amplitude of lateral movement of the head and frequency of flagellar beat, in which higher values (p<0.05) were obtained for fish induced with EHC. On the other hand, for the variables coefficient of linearity, coefficient of straightness and mean oscillation of the spatial trajectory of the sperm, the values were higher (P<0.05) in fish induced with EHC in relation to those induced with 0.02 and 0, 08 of kisspeptin and saline, but did not differ from the level of 0.05 mg/kg. It is concluded that the evaluated kisspetin concentrations were not effective to improve the reproductive variables of males of yellow-tailed lambari. Keywords: Reproductive characteristics, hormonal induction, Kisspetina, rheophilic fish.